A Comparative Study of Hydroxyapatite‐ and Alumina‐Based Catalysts in Dry Reforming of Methane. Issue 4 (17th February 2020) - Rego de Vasconcelos, Bruna; Pham Minh, Doan; Martins, Emmanuel; Germeau, Alain; Sharrock, Patrick; Nzihou, Ange
Abstract: The dry reforming of methane over hydroxyapatite‐ and alumina/magnesia (commercial Pural MG 30)‐supported nickel catalysts was investigated. The catalytic performance of the catalysts prepared with fresh supports highly depended on the basicity, the metal‐support interaction, and the metal particle size. Calcination of the supports at 1200 °C for 5 h made the catalysts less active because of specific surface area reduction and basicity destruction. However, this treatment allowed avoiding any further catalyst deactivation by thermal sintering and maintained excellent catalytic stability over 300 h of time‐on‐stream. These tests under simulated industrial conditions (high contact time and long time‐on‐stream) showed the competitiveness of the prepared catalysts in this important catalytic process. Abstract : Dry reforming of methane has been intensively studied during the last decade, but it is still not deployed on the industrial scale. One of the main challenges of the process is the development of an active and stable reforming catalyst. Hydroxyapatite is reported as a new promising material to design highly active and stable catalysts for this process.